Presentation and outcomes of necrotizing soft tissue infections - Chen KJ; Klingel M; McLeod S; Mindra S; Ng VK (International Journal of General Medicine, 2017)
Kuan-Chin Jean Chen,1 Michelle Klingel,2 Shelley McLeod,3 Sean Mindra,4 Victor K Ng5 1Department of Emergency Medicine, Faculty of Medicine, The Ottawa Hospital, University of Ottawa, Ottawa, 2Division of Respiratory Medicine, Department of Pediatrics, Hospital for Sick Children, University of Toronto, 3Department of Family and Community Medicine, University of Toronto, Schwartz/Reisman Emergency Medicine Institute, Mount Sinai Hospital, Toronto, 4Department of Family Medicine, Faculty of Medicine, University of Ottawa, Ottawa, 5Division of Emergency Medicine, Faculty of Medicine, London Health Sciences Centre, Western University, London, ON, Canada Background: Necrotizing soft tissue infections (NSTIs) are aggressive infections associated with significant morbidity, including amputation and organ failure, and high mortality. The rapid progression and significant risk of morbidity and mortality associated with NSTIs makes quick diagnosis and treatment critical. The objective of this study was to determine the presentation of patients diagnosed with NSTIs and their in-hospital outcomes. Methods: This was a retrospective review of adult (>17 years) patients with a discharge diagnosis of necrotizing fasciitis at London Health Sciences Centre (annual census 125,000) over a 5-year period (April 2008–March 2013). Results: Sixty patients with confirmed NSTI were included in this study. Common comorbidities at presentation included immunocompromise (58.3%), diabetes mellitus (41.7%), vascular disease (45.0%), and obesity (24.6%). Initial presentations included swelling (91.7%), erythema (86.7%), bullae (28.3%), petechiae (8.3%), and bruising (45.0%). Fifty (83.3%) underwent surgery, with a median (interquartile range) time from initial emergency department presentation to surgery of 15.5 hours (7.8, 74.9). In-hospital mortality among those who had surgical intervention was 14.0%, compared to 60.0% for patients who did not have surgery (Δ46.0%; 95% CI: 14.8% to 70.2%). Conclusion: Diabetes mellitus, immune-compromise, vascular disease, and obesity are common comorbidities of NSTIs. Survival is higher among patients who receive surgical treatment. Patients presenting with this clinical picture warrant a high degree of suspicion. Keywords: clinical evaluation and treatment, skin diseases, infectious diseases of the skin